Sr-Nd-Pb-He-O Isotope and Geochemical Constraints on the Genesis of Cenozoic Magmas from the West Antarctic Rift - Nardini I; Armienti P; Rocchi S; Dallai L; Harrison D (Journal of Petrology, 2009)
The West Antarctic Rift System (WARS) represents one of the major active continental extension zones on Earth. The Ross Sea coast in northern Victoria Land (NVL) is littered with alkaline rift-related igneous products (Middle Eocene-Present). This study characterizes the nature of the magma source involved in the rift process through geochemical-isotopic investigation of Cenozoic basalts from NVL, and provides important constraints for the reconstruction of the tectono-magmatic evolution of the Ross Sea region-WARS. The chemical compositions of the basalts (Miocene-Present) display major and trace element characteristics typical of ocean island basalts (OIB), with strong enrichment in the most incompatible elements. Whole-rock isotopic compositions are in the range 0.7028-0.7034 for (87)Sr/(86)Sr, 0.5129-0.5130 for (143)Nd/(144)Nd (epsilon Nd(t) similar to 4.8-6.7), 19.3-19.7 for (206)Pb/(204)Pb, 15.4-15.6 for (207)Pb/(204)Pb and 38.7-39.3 for (208)Pb/(204)Pb, suggesting a HIMU-like (high U/Pb) signature of the mantle source. Determinations of (3)He/(4)He on crushed olivine yielded values between 5.7 and 7.2 times the atmospheric ratio, similar to the lithospheric mantle and in the range of mid-ocean ridge basalts (MORB). The delta(18)O(ol) of olivine separates varies from 4.92 to 5.53% and is positively correlated with Fo content. Integration of our geochemical and isotope data with available geological, geophysical and geochronological data has led to the following reconstruction. The differences in the oxygen isotope values principally reflect the involvement of a heterogeneous mantle source and/or the assimilation of variable amounts of hydrothermally altered crustal rocks from the volcanic edifices. The (3)He/(4)He data allow us to exclude a plume-driven model to explain the continuing rifting process. Based on the evidence of metasomatic processes, we propose a model to generate the mantle source(s) of the Cenozoic basaltic melts of the NVL. This is sublithospheric mantle metasomatized during an amagmatic ...